2014
DOI: 10.1063/1.4897435
|View full text |Cite
|
Sign up to set email alerts
|

Determining conductivity and mobility values of individual components in multiphase composite Cu1.97Ag0.03Se

Abstract: Articles you may be interested inEnhanced low temperature thermoelectric performance of Ag-doped BiCuSeO Appl. Phys. Lett. 105, 082109 (2014); 10.1063/1.4894258Terahertz and direct current losses and the origin of non-Drude terahertz conductivity in the crystalline states of phase change materials

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The enhanced S values of PbSe/PbTe samples compared to that of PbSe samples appear to arise from the energy barriers at the interfaces, including the precipitate/matrix interfaces and grain boundaries. Moreover, some reports showed that impurity phases (Pb impurity phases in our case) can influence the transport properties within a semiconductor. ,,, An in-depth discussion of this is included in the next section. It should be emphasized that the increase in σ for the bulk PbSe/PbTe samples starts at 523 K, which is identical to the temperature at which the rate of increase of S decreases, as shown in Figure c (this is discussed in detail later).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The enhanced S values of PbSe/PbTe samples compared to that of PbSe samples appear to arise from the energy barriers at the interfaces, including the precipitate/matrix interfaces and grain boundaries. Moreover, some reports showed that impurity phases (Pb impurity phases in our case) can influence the transport properties within a semiconductor. ,,, An in-depth discussion of this is included in the next section. It should be emphasized that the increase in σ for the bulk PbSe/PbTe samples starts at 523 K, which is identical to the temperature at which the rate of increase of S decreases, as shown in Figure c (this is discussed in detail later).…”
Section: Resultsmentioning
confidence: 94%
“…These systems are similar to those in the present study because PbSe/PbTe samples have an excess of Pb atoms, Te-rich PbSe/PbTe precipitates with a wide size distribution, and many grain boundaries. Using effective medium theory, Day et al successfully separated conductivity and mobility of independent phases and showed an impurity phase can severely influence TE transport properties. About an application of the effective medium theory to multiple-component TE materials, Gelbstein et al , explained well in some papers.…”
Section: Resultsmentioning
confidence: 99%
“…In order to minimize the influence of secondary phases on the thermoelectric properties, nominal compositions were chosen to be very close to the stable points and due to the lever rule, the amount of secondary phases is small and their effect can thus be neglected. For small amounts of secondary phases, it can be shown using effective medium theory that the first order effect on electrical and thermal transport properties is proportional to the volume fraction of impurity [20]. Thus for 1% volume fraction the measured transport properties should only be 1% in error.…”
Section: Thermoelectric Properties Of Optimized Compositionsmentioning
confidence: 98%
“…To describe the effects of having a mixture of two materials (in this case the experimental material and air), effective medium theory (EMT) is used to analyze the electrical and thermal conductivity of porous materials. Generalized EMT developed by Bruggeman and Landauer, and described by Stroud was used to explain the low field Hall effect by Cohen .…”
mentioning
confidence: 99%